A systematic review of economic evaluation in pancreatic ductal adenocarcinoma. (November 2017) - Gérard, Claire; Fagnoni, Philippe; Vienot, Angélique; Borg, Christophe; Limat, Samuel; Daval, Franck; Calais, François; Vardanega, Julie; Jary, Marine; Nerich, Virginie
Abstract: Objectives: The economic evaluation (EE) of healthcare interventions has become a necessity. However, high quality needs to be ensured in order to achieve validated results and help making informed decisions. Thus, the objective of the present study was to systematically identify and review published pancreatic ductal adenocarcinoma-related EEs and to assess their quality. Methods: Systematic literature research was conducted in PubMed and Cochrane to identify published EEs between 2000 and 2015. The quality of each selected EE was assessed by two independent reviewers, using the Drummond's checklist. Results: Our systematic review was based on 32 EEs and showed a wide variety of methodological approaches, including different perspectives, time horizon, and cost effectiveness analyses. Nearly two-thirds of EEs are full EEs (n = 21), and about one-third of EEs had a Drummond score ≥7, synonymous with 'high quality'. Close to 50% of full EEs had a Drummond score ≥7, whereas all of partial EEs had a Drummond score <7 (n = 11). Conclusions: Over the past 15 years, a lot of interest has been evinced over the EE of pancreatic ductal adenocarcinoma (PDAC) and its direct impact on therapeutic advances in PDAC. To provide a framework for health care decision-making, to facilitate transferability and to lend credibility to health EEs, their quality must be improved. For the last 4 years, a tendency towards a quality improvement of these studies has been observed, probably coupled with a context of rational decision-making in health care, a better and wider spread of recommendations and thus, medical practitioners' full endorsement. Highlights: Only 32 economic evaluations (EEs) have been published over the past 15-years. A wide variety of methodological approaches were shown. Nearly two-thirds of EEs are full and 40% are cost-utility analyses. Only nearly one-third of EEs are of high quality. Need to apply European and international recommendations to ensure quality of EEs.